Spatiotemporal control of Atg2 association with the ER during autophagosome formation - Tetsuya Kotani; Haruki Tanabe; Shinri Kitta; Momoko Higashi; Tatsuya Niwa; Tatsuya Kaminishi; Chika Kakuta; Junko Shimasaki; Hidetaka Kosako; Tamotsu Yoshimori; Akiko Kuma; Hitoshi Nakatogawa (Proceedings of the National Academy of Sciences, 2026)
Autophagy degrades various intracellular components by sequestering them within membrane vesicles called autophagosomes and delivering them to lysosomes or vacuoles. Previous studies have revealed that the conserved, bridge-like lipid transfer protein Atg2 tethers autophagosome precursors to the endoplasmic reticulum (ER) and mediates lipid supply from the ER to drive their expansion into autophagosomes. However, how Atg2 docks onto the ER has remained unclear. Here, we show in Saccharomyces cerevisiae that Atg2 interacts with the ER-resident VAP family protein Scs2. This interaction is mediated by a phospho-FFAT motif in Atg2 and the major sperm protein domain of Scs2 and enhanced by phosphorylation of the motif by the autophagy-initiating kinase Atg1, which is activated at the autophagosome formation site upon autophagy induction. This interaction cooperates with the N-terminal region of Atg2, which contains a weakly amphipathic helix, to mediate Atg2 association with the ER. Thus, the Atg2–Scs2 interaction functions as a spatiotemporal switch that controls Atg2–ER association. We also show that mammalian ATG2 interacts with the VAP-like proteins MOSPD1 and MOSPD3 to promote autophagosome formation. Collectively, this study reveals a conserved mechanism that initiates lipid transfer during autophagosome formation.